Evaluation of mating behaviour and mating compatibility methods for the Old World screwworm fly, Chrysomya bezziana. - April H. Wardhana; Cameron MM; Muharsini S; Hall MJR (Jurnal Ilmu Ternak dan Veteriner, 2013)
The effectiveness of the Sterile Insect Technique program (SIT) to eradicate pest insects relies on the success of mating competitiveness between irradiated male flies and wild type males for the wild type females. It has been successfully applied for the New World screwworm fly (NWSF), Cochliomyia hominivorax but remains unproven for the Old World screwworm fly (OWSF), Chrysomya bezziana. The aim of the study was to develop methods for investigating mating behaviour and mating compatibility of C. bezziana under laboratory conditions. Two methods were used for studying mating: individual mating (method 1) and group mating (method 2). The flies used in this study were 5-7 days old. Twenty four hours after emergence, adult flies were sexed and placed into different cages until studied. The female : male ratio in the group mating was 1 : 5 and the males were marked by painting a dot on the thorax using different oil colours. Observation of mating behaviour was investigated every 30 minutes through 10-20 replications for all methods depending on the availability of flies. Data were analysed using ANOVA and the Student’s t-test, with significance demonstrated at the 95% confidence level. The results demonstrated that the frequency of contacts between males and females at different ages was a significantly different (p < 0.05) and that the duration of copulation was not significantly affected by fly age both method 1 (p > 0.05) and method 2 (p > 0.05). Copulation was only initiated following longer periods of contact, mainly in the range of 270-449 seconds. The highest frequency of copulation occurred between 7-8 days, but the duration of mating was similar between 5-8 days old. The study demonstrated that the methods developed were suitable for a mating compatibility study of C. bezziana. Key Words: Chrysomya bezziana, Mating Behaviour, Copulation, Myiasis